Além da estereotipia: o modelo de fã criativo a partir do percurso de Morrissey - Spinola Caria, Renata (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
Based on the analysis of the artistic production of english singer and pop music world icon, Steven Patrick Morrissey, this text deals with the fan work and fandom in the contemporaneity. Far from being characterized by alienation or passiveness, the fan takes a creative attitude when he or she constructs new discourses based on those they admire. Using a transdisciplinary approach, this texts aims to read Morrissey’s works as a result of a constant dialogue with his idols, what enables the emergence of an intertextual production and the construction of his persona as an idol himself and as an example of a creative fan. Key-words: Fan. Fandom. Morrissey. Cerative fan.
Keywords: Fan; Fandom; Morrissey; Creative fan